PENGEMBANGAN LEMBAGA KEUANGAN MIKRO SYARIAH DI SUMATERA BARAT BERBASIS KEARIFAN LOKAL “TUNGKU TIGO SAJARANGAN” - Mursal Mursal (Journal Analytica Islamica, 2016)
West Sumatra is famous for its local ethnic religious wisdom as Adat Basandi Syarak, Syarak Basandi Kitabullah. In addition, in the realm of ethnic leadership Minagkabau also have a cultural concept Tungku Tigo Sajarangan, which is functionally role in shaping patterns and behavior society. In assumptive, local wisdom as well as the religious character of Minangkabau society committed to abide by the teachings of indigenous and indigenous leaders, will give strength to the economic development of sharia. however, there are strong indicators that show that the Islamic Microfinance Institutions in West Sumatra has not developed as ideal as assumed. Synergy between components “Tungku Tigo Sajarangan” on the one hand, and with the Islamic Micro Finance Institutions on the other hand, can be used as capital and models of economic development of sharia and will contribute positively to the development of Indonesia, particularly in West Sumatra.